Creating a Culture of Evidence-Based Teaching through Faculty Professional Development - Kirsten Fleming; David Polcyn (Academic Chairpersons Conference Proceedings, 2017)
This session will focus on leading change designed to instill a culture of equity-minded, evidence-based teaching and learning. Drawing on a community of practice model, a variety of professional development opportunities will be explored that enable STEM faculty members to redesign courses in ways that intentionally incorporates evidence-based teaching practices.
Keywords: Change; culture; evidenced-based teaching; diversity; inclusivity; professional development